The struggle of Nahdlatul Ulama in Maintaining a Sustainable Scientific Tradition in a Complex Transdisciplinary Era - Suyuti, Imam (Proceeding International Conference on Religion, Science and Education, 2022)
Nahdlatul Ulama has recently been aggressively promoting the “Islam Nusantara” paradigm. This of course caused a polemic in the Indonesian public and received various criticisms, especially from those who have different points of view with Nahdlatul Ulama. The problems raised in this research are why it is important to actualize scientific traditions in a sustainable manner and how is the mechanism of the ulama-santri affiliated with Nahdlatul Ulama in maintaining a sustainable scientific tradition in a complex transdisciplinary era. The purpose of this research is to explore the struggles of Nahdlatul Ulama teachers-students in maintaining scientific traditions in a complex transdisciplinary era and to describe these struggles in a mechanism consisting of pesantrens and the “Islam Nusantara” paradigm. The results of this study indicate that pesantren is a forum and basis for Nahdlatul Ulama in maintaining scientific traditions in the complex transdisciplinary era. What is in the pesantren is the result of a mixture of religious architects who really understand how to maintain scientific traditions in a sustainable manner. The scientific tradition of pesantren actually departs from small recitations in the surau in the context of guidance for worship, which is later able to grow and develop, even being reborn into a socio-religious institution that has succeeded in playing an active role in shaping the morality and values of a great nation, namely Nusantara and now Indonesia. The pesantren is fully committed to its own values to be widely used in the community. The mechanism for Nahdlatul Ulama scholars in maintaining the scientific tradition in pesantrens is carried out by framing the “Islami Nusantara” paradigm. This is very closely related to the tradition of pesantrens such as those built by Walisongo and the preachers in the next period until they arrived at the complex transdisciplinary era today.